2016
DOI: 10.5296/ajfa.v8i1.9129
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Estimation of Volatility Using ARCH/GARCH Models in Jordan’s Stock Market

Abstract: <p>Financials have been concerned constantly with factors that have impact on both taking and assessing various financial decisions in firms. Hence modelling volatility in financial markets is one of the factors that have direct role and effect on pricing, risk and portfolio management. Therefore, this study aims to examine the volatility characteristics on Jordan’s capital market that include; clustering volatility, leptokurtosis, and leverage effect. This objective can be accomplished by selecting symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Consistent with many previous studies (see for example, Franses & Van Dijk [43], Gokcan [44] and AL-Najjar [45], the study applies the GARCH (1,1). This …”
Section: The Garch (11) Estimation Resultssupporting
confidence: 65%
“…Consistent with many previous studies (see for example, Franses & Van Dijk [43], Gokcan [44] and AL-Najjar [45], the study applies the GARCH (1,1). This …”
Section: The Garch (11) Estimation Resultssupporting
confidence: 65%
“…Dana Alnajjar (2016) attempted to forecast the volatility of Jordan's capital market using GARCH family models. The study comprises of three models i.e ARCH, GARCH and EGARCH to find out volatility clustering, leptokurtosis and leverage effect on Amman stock exchange which showed that ARCH GARCH gives more evidence for both volatility clustering and leptokurtic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The choice of lower GARCH models stems from the fact that GARCH (1,1) model is sufficient for capturing all volatilities present in any financial data and also producing the desired relationship between risk and expected returns. For evidence see the works by many researchers [31,32,33,34,35,36,37,38,39] among others.…”
Section: Model Specificationmentioning
confidence: 99%